Basel III and Systemic Risk Regulation - What Way Forward? - Co-Pierre Georg (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
One of the most pressing questions in the aftermath of the financial crisis is how to deal with systemically important financial institutions (SIFIs). The purpose of this paper is to review the recent literature on systemic risk and evaluate the regulation proposals in the Basel III framework with respect to this literature. A number of shortcomings in the current framework are analyzed and three measures for future reform are proposed: counter-cyclical risk-weights, dynamic asset value correlation multipliers, and enhanced transparency requirements for SIFIs.
urn:nbn:de:gbv:27-20131118-112305-8
Keywords: C63; E52; E58; G01; G21; 330; systemic risk; SIFIs; regulation; Basler Akkord; Bankenregulierung; Basler Akkord; Bank; Systemrisiko; Regulierung; Welt